Epichloë – a key element of New Zealand’s agricultural landscape - Stuart D. Card; Daniel A. Bastías; Wei Zhang; David E. Hume; John R. Caradus (New Zealand Journal of Botany, 2024)

Can Aphid Herbivory Induce Intergenerational Effects of Endophyte-conferred Resistance in Grasses? - Ludmila M. Bubica Bustos; Andrea C. Ueno; Fernando Biganzoli; Stuart D. Card; Wade J. Mace; María A. Martínez-Ghersa; Pedro E. Gundel (Journal of Chemical Ecology, 2022)

Factors controlling the effects of mutualistic bacteria on plants associated with fungi - Daniel A. Bastías; Emma R. Applegate; Linda J. Johnson; Stuart D. Card (Ecology Letters, 2022)
Plants interacting with mutualistic fungi (MF) or antagonistic fungi (AF) can form associations with bacteria. We assessed whether the performance gain conferred by mutualistic bacteria to fungal‐associated plants is affected by the interaction between symbiont traits, type of bacterial‐protective traits against AF and abiotic/biotic stresses. Results showed that (A) performance gain conferred by bacteria to MF‐associated plants was greater when symbionts promoted distinct rather than similar plant functions, (B) bacterial‐based alleviation of the AF's negative effect on plants was independent of the type of protective trait, (C) bacteria promoted a greater performance of symbiotic plants in presence of biotic, but not abiotic, stress compared to stress‐free situations. The plant performance gain was not affected by any fungal‐bacterial trait combination but optimised when bacteria conferred resistance traits in biotic stress situations. The effects of bacteria on fungal‐associated plants were controlled by the interaction between the symbionts' functional traits and the relationship between bacterial traits and abiotic/biotic stresses.

Novel perennial ryegrass-Neotyphodium endophyte associations: relationships between seed weight, seedling vigour and endophyte presence - Stuart D. Card; M. Philip Rolston; Catherine Lloyd-West; David E. Hume (Symbiosis, 2014)